SISTEM PAKAR UNTUK MENENTUKAN KEPRIBADIAN SESEORANG BERDASARKAN TES PERSONALITAS FLORENCE LITTAUER BERBASIS WEB - Sigit Iskandar; Muhammad Sholeh; Catur Iswahyudi (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2015)
Personality is very important to be known by everyone so that every individual is able to develop its advantages. Someone who had difficulty in developing itself the possibility of not knowing at all its weaknesses and shortcomings. Expert System is a system that is built to remove the ability of one or several experts in the computer that is used to solve the problems faced by users in a specific field. To help everyone who wants to know his personality, the authors build A web based expert system for determining human personality based on Florence Littauer personality test that is able to assist the introduction of one's personality. The process of making these applications using object-oriented methodologies with modeling Unified Modeling Language (UML). In the implementation phase the authors use a web-based programming using Ruby on Rails. This application can help the user to know his personality, so it can help to develop themselves.